Isolation and Characterization of Human Intestinal Bacteria Cytobacillus oceanisediminis NB2 for Probiotic Potential - Yadav, Monika; Kumar, Tarun; Kanakan, Akshay; Maurya, Ranjeet; Pandey, Rajesh; Chauhan, Nar Singh (Frontiers in Microbiology, 2022)
Systemic characterization of the human gut microbiota highlighted its vast therapeutic potential. Despite enormous potential, the non-availability of their culture representatives created a bottleneck to realize the concept of microbiome based therapeutics. The present study is aimed to isolate and evaluate the probiotic potential of a human gut isolate. Physiochemical, morphological, and phylogenetic characterization of a human gut isolate identifies it as a rod shaped gram-negative microbe taxonomically affiliated with the Cytobacillus genus, having an optimal growth at 37°C in a partially alkaline environment (pH 8.0). This human gut isolate showed continuous growth in the presence of salts (up to 7% NaCl and 10% KCl) antibiotics, metal & metalloids (Silver nitrate (up to 2mM); Lead acetate (up to 2mM); Sodium arsenate (up to 10mM); Potassium dichromate (up to 2mM)), gastric and intestinal conditions, diverse temperature (25°C to 50°C), and pH (5-9) conditions, making it fit to survive in the highly variable gut environment. Genomic characterization identified the presence of gene clusters for diverse bio-catalytic activity, stress response, and antimicrobial activity, as well as indicated the absence of pathogenic gene islands. A combination of functional features like anti-amylase, anti-lipase, glutenase, prolyl endopeptidase, lactase, bile salt hydrolase, cholesterol oxidase, and anti-pathogenic activity is indicative of its probiotic potential in various disorders. This was further substantiated by the CaCo-2 cell line assay confirming its cellular adherence and biosafety. Conclusively, human gut isolate possessed significant probiotic potential that can be used to promote animal and human health.